Looking at the Social Activity for Adolescents with Orthopedic Impairments - Leslie Biastro; Heather Frank; Karen H Larwin (International Journal of Evaluation and Research in Education (IJERE), 2015)
Adolescents with identified orthopedic impairments are often less likely to participate in social activities outside of the school setting. However, the adolescents who are able to participate in activities have higher social skills, more academic successes, and show more satisfaction in their roles as family member or friend. The aim of this study was to look at adolescents with orthopedic impairments and their level of participation in social activities.   Also looked at was the adolescent’s report of a higher level of fulfillment in their family or friend role if they participated in social activities.  Responses of adolescents from a national school-based survey were used in the study.  The results revealed that students with orthopedic impairments were just as happy as their peers when they participated in social activities.